FINANCIAL FEASIBILITY AND DEVELOPMENT STRATEGY OF HYDROPONIC FARM MANAGEMENT CV. LANGGENG HIDROPONIK KEDIRI MUNICIPLE - Kusmiati, Ati; Evana Tasya, Sendy; Fauziyah, Diana (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
Kediri Municiple is a one of municipality in East Java Province has started cultivating vegetables in a hydroponic system. Even if there is still a lot of room for hydroponic veggies in Kediri, there are a lot of obstacles to overcome before you can start using a hydroponic system to grow your vegetables. One of them is the significant financial outlay required to start a hydroponic farming business. The research was aimed to: (1) the financial feasibility of hydroponic vegetable farming; (2) the sensitivity of hydroponic vegetable farming to a 10% decrease in production and a 20% increase in production costs; and (3) the best business development strategy for CV. Langgeng Hidroponik Kediri Municiple. The results of this research showed that: 1) hydroponic vegetable farming CV. Langgeng Hidroponik is feasible to cultivate with a positive NPV for five years, namely Rp77.886.534.77; with a Net B/C value of higher than 1 (2,22); IRR is higher than the interest rate (7 percent), which was 36,41%; and PP was longer than the economic age of hydroponic vegetable farming (5 years) which was 3,5 years. (2) the results of the analysis showed that vegetables farming in CV Langgeng Hidroponik was sensitive to an 10% decrease in production and a 20% increase in production costs. (3) based on the TAS value, the best strategy to be implemented and become the priority in CV Langgeng Hidroponik was entails intensive collaboration with other hydroponic farmers in order to develop human research competencies